Could a customer's migratory behaviour in inner areas explain his/her purchase: an exploratory analysis. (2016) - Ohno, Asako; Ohata, Yoshihiro; Yamasaki, Takahiro; Tokiwa, Kin-ichiroh
Generally, the majority of customers move along the areas located outside of the main circular path on the sales floor of a supermarket. At the same time, statistically it has been determined that a longer shopping path leads to a higher purchase volume and higher volume customers have the possibility of spending more time within the inner part of a sales floor. Thus, we expect an improvement in purchasing by opening shopping paths into the inner areas to enhance customers' chances to discover new products. Realising an effective path extension to increase customers' purchases requires us to perceive the features of higher and lower volume customers. The study aims to establish a classification rule based on customers' behavioural features within inner areas. The paper provides an explanation of our method to quantify customers' behavioural features and reports the outcomes from the exploratory analysis using real-world shopping path and purchase data.